2008
DOI: 10.1016/j.brainresbull.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological examinations of rat brains after long-term exposure to GSM-900 mobile phone radiation

Abstract: 2 AbstractIn order to mimic the real life situation, with often life-long exposure to the electromagnetic fields emitted by mobile phones, we have investigated in a rat model the effects of repeated exposures under a long period to Global System for Mobile Communication-900 MHz (GSM-900) radiation. Out of a total of 56 rats, 32 were exposed once weekly in a two hours period, for totally 55 weeks, at different specific absorption rates (SAR) (of in average 0.6 and 60 mW/kg at the initiation of the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…The animals were exposed to RF EMFs in the same transverse electromagnetic transmission line cell (TEMcells) as previously described and used by Salford et al (1992Salford et al ( , 1993Salford et al ( , 1994Salford et al ( , 2003, Persson et al (1997), Eberhardt et al (2008), Grafström et al (2008), Nittby et al (2008aNittby et al ( , 2009) (for further descriptions see Malmgren 1998; Van Hese et al 1992, Martens et al 1993). The TEM-cells were designed by dimensional scaling from previously constructed cells at the National Bureau of Standards (Crawford 1974).…”
Section: Gsm Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The animals were exposed to RF EMFs in the same transverse electromagnetic transmission line cell (TEMcells) as previously described and used by Salford et al (1992Salford et al ( , 1993Salford et al ( , 1994Salford et al ( , 2003, Persson et al (1997), Eberhardt et al (2008), Grafström et al (2008), Nittby et al (2008aNittby et al ( , 2009) (for further descriptions see Malmgren 1998; Van Hese et al 1992, Martens et al 1993). The TEM-cells were designed by dimensional scaling from previously constructed cells at the National Bureau of Standards (Crawford 1974).…”
Section: Gsm Exposurementioning
confidence: 99%
“…In one of our earlier experiments, the long-term exposure to GSM-900 mobile phone radiation (Grafström et al 2008), we omitted the fans and utilized the suction table underneath the cages for air circulation. We found that albumin foci were sparse in both the SAR 60 mW/kg and 0.6 mW/kg groups.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the astroglial response to GSM, the literature is characterized by a high variability, as shown by negative (Fritze et al, 1997;Grafstrom et al, 2008) and positive effects (Ammari et al, 2010;Brillaud et al, 2007;Mausset-Bonnefont et al, 2004). Protocol differences may explain part of this variability, as, GFAP expression can be decreased by stress (Laping et al, 1994).…”
Section: Gsm Exposure and Neuro-immune Systemmentioning
confidence: 99%
“…[16][17][18] Whereas, a study by Grafström et al showed no significant alteration in the histopathological parameters, when comparing the GSM-exposed animals to the sham-exposed controls. [19] The International Agency for Research on Cancer which is a part of the World Health Organization has grouped these radiations as Group 2B carcinogens implying that they are possibly carcinogenic. [20] In a study done on molluscan neuron, the high SARs produced by cell phone-like RF field simulations led to a delay in the cellular mechanism for processing and storage of information.…”
Section: Discussionmentioning
confidence: 99%